1996
DOI: 10.1126/science.274.5286.427
|View full text |Cite
|
Sign up to set email alerts
|

Neural Control of Voluntary Movement Initiation

Abstract: When humans respond to sensory stimulation, their reaction times tend to be long and variable relative to neural transduction and transmission times. The neural processes responsible for the duration and variability of reaction times are not understood. Single-cell recordings in a motor area of the cerebral cortex in behaving rhesus monkeys (Macaca mulatta) were used to evaluate two alternative mathematical models of the processes that underlie reaction times. Movements were initiated if and only if the neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

82
987
8
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,087 publications
(1,085 citation statements)
references
References 9 publications
82
987
8
8
Order By: Relevance
“…For example, there are cells within the frontal eye fields of the monkey whose firing rate exhibits rise-tothreshold behaviour in advance of a saccade, and whose rate of rise corresponds closely with saccadic latency (Hanes and Schall 1996).…”
Section: Reciprobit Plots Of Saccadic Latencymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there are cells within the frontal eye fields of the monkey whose firing rate exhibits rise-tothreshold behaviour in advance of a saccade, and whose rate of rise corresponds closely with saccadic latency (Hanes and Schall 1996).…”
Section: Reciprobit Plots Of Saccadic Latencymentioning
confidence: 99%
“…The ultimate brain region influenced by L-dopa in this instance is not known, but an appealing candidate is the frontal eye fields, where the firing rate of single neurons in the monkey show rise-to-threshold behaviour in advance of a saccade that correspond closely with LATER's decision signal (Hanes and Schall 1996). Furthermore, in primates, D2 receptor activation can modulate the activity of prefrontal neurons to memory-guided saccades (Wang et al 2004).…”
Section: The Site Of Action Of Dopaminementioning
confidence: 99%
“…Provocative results from this area suggest that sequential sampling models like diffusion models are a good representation of the neural mechanisms underlying sensory decisions (Gold & Shadlen, 2007), which appear to be embedded in the sensory-motor circuitry in the brain (Hanes & Schall, 1996;Kim & Shadlen, 1999;Romo, Hernandez, Zainos, Lemus, & Brody, 2002;Shadlen & Newsome, 2001). These results have led to the hypothesis that these sensorymotor areas are the mediating mechanisms for other types of abstract and value-based decisions (Busemeyer, Jessup, Johnson, & Townsend, 2006;Shadlen, Kiani, Hanks, & Churchland, 2008).…”
Section: A Common Choice and Judgment Processmentioning
confidence: 99%
“…Figure 11.7E shows the activity of a neuron in the frontal eye fields (FEF) for fast, medium, and slow responses to a visual target [39,40]. Schall and collaborators have shown that the distribution of monkey response times can be reproduced using the time taken by neural activity in FEF to reach a fixed threshold [15]. A similar rise-to-threshold model by Carpenter and colleagues has received strong support in human psychophysical experiments that manipulate the prior probabilities of targets [3] and the urgency of the task [35].…”
Section: Comparison To Neurophysiological Datamentioning
confidence: 99%
“…The posterior probabilities of the unknown variables C, L, and F given the input image I, are calculated by combining the messages at each node as follows: 15) where α, β, and γ are normalization constants that make each of the above probabilities sum to 1. Note how the prior P (L) multiplicatively modulates the posterior probability of a feature in equation 11.15 via equation 11.12.…”
Section: Hierarchical Belief Propagationmentioning
confidence: 99%